DEVELOPMENT OF LABORATORY POWER SUPPLY UNIT WITH REGULATED PARAMETERS BASED ON THE LM317TVOLTAGE STABILIZER - Kobets, T.S.; Burak, D.V. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
In this article, the assembly scheme and the results of testing a laboratory power supply based on the LM317T voltage regulator are proposed.The power unit was assembled in the laboratory №813 of the Department of Natural Sciences of the Kostanay State Pedagogical Institute.Explanations of the purpose of each component of the circuit are given for the possibility of reproducing this unit. Technical characteristics are given. The possibility of improving the device by replacing certain radio components with more powerful ones is shown. Didactic materials on the use of this power supply unit are presented in the laboratory practical work on physical chemistry.
Keywords: power supply; direct current; laboratory equipment; laboratory practice; physical chemistry; electrochemistry